Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.4314/ahs.v14i3.14
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and prevalence of risk factors for arterial hypertension and blood pressure pattern among bankers and traffic wardens in Ilorin, Nigeria

Abstract: Background: High job strain, mental stress, sedentary lifestyle, increase in BMI are among the factors associated with significantly higher incidence of hypertension. The job of bank employees is both sedentary in nature and accompanies high mental stress. The aim of this study is to assess the level of knowledge of risk factors among respondents and to compare the blood pressure pattern of bankers and traffic wardens. Methodology: The study design is a descriptive cross-sectional conducted among bankers and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 18 publications
8
27
2
2
Order By: Relevance
“…Their job specification can be stressful and can be associated with elevated blood pressure. [9][10][11][12]20] A total of 194 bank workers were studied with slightly more males (51.5%) compared to the females (48.5%). More than half the number of workers studied, 105 (54.1%), were less than 30 years of age suggesting that most bank workers are in their third decade of life when they are most suited to withstand the associated stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their job specification can be stressful and can be associated with elevated blood pressure. [9][10][11][12]20] A total of 194 bank workers were studied with slightly more males (51.5%) compared to the females (48.5%). More than half the number of workers studied, 105 (54.1%), were less than 30 years of age suggesting that most bank workers are in their third decade of life when they are most suited to withstand the associated stress.…”
Section: Discussionmentioning
confidence: 99%
“…[9] However, among bankers in Ilorin, North Central Nigeria, the prevalence of hypertension was observed to be 34.4%. [10] In Nigeria, awareness of blood pressure status was observed to be 7.7% among men and 8.7% among women but significantly higher among previously diagnosed hypertensives. [4] Among bank workers in Benin city, Edo state, 48.4% had correct knowledge of hypertension, 70.8% had good knowledge of its complications and 65.1% had good knowledge of its risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian lain menyebutkan bahwa pendidikan tidak berpengaruh signifikan ter hadap tekanan darah (Lee, 2017). Meskipun beberapa hasil penelitian tidak menunjukkan hasil yang sesuai, beberapa faktor ini disebut memengaruhi peningkatan tekanan darah, yaitu rokok, alkohol, obesitas, makanan tinggi garam, obat-obatan, stres, permasalahan emosional, dan riwayat keluarga (Salaudeen, dkk., 2014).…”
Section: Hasil Dan Pembahasanunclassified
“…According to the figures, it can be deduced that lack of physical activity has a strong association with more than 30% of annual deaths [6]. Multiple researches have been conducted to evaluate the affiliation between lack of physical activity and incidence/prevalence of morbidities [7]. In an International Cross-Sectional Study, the odds ratio of CHD in sedentary women was found to be 2.1% (95% CI 1.0-4.3, P=0.046) [8].…”
Section: Association Of Physical Activity With Co-morbid Conditions Imentioning
confidence: 99%